FEASIBILITY ANALYSIS OF BUSINESS "AMALIA BOUTIQUE"PTWARNA WARNI AMALIA AS MUSLIMAH FASHIONIN SOUTH JAKARTA - Dian Amalia Handayani (JRMSI - Jurnal Riset Manajemen Sains Indonesia, 2016)
This research aims to determine the feasibility of Muslimah fashion business "Amalia Boutique" by analyzing from several aspects including the legal aspects, environmental aspects, market aspects and marketing, technical and technological aspects, and aspects of human resource management, and financial aspects. Object of this study is "Amalia Boutique", is engaged in the business of fashion Muslimah. The design of this research is a descriptive study using qualitative techniques.Primary data collection techniques in this study is the observation to determine the location of Muslim fashion boutiques and stores in South Jakarta and the observation of the use of hijab. As for the secondary data obtained by researchers obtained from several sources such as the BPS, books, reports, journals, and the internet.The results of the analysis of the feasibility study "Amalia Boutique" is feasible when viewed from the sixth aspect.  Keywords: feasibility study, Payback Period (PP), Net Present Value (NPV),Pofitability Index (PI), Internal Rate of Return (IRR), Accounting Rate of Return(ARR).